-11g+14-20=-11g-6

Simple and best practice solution for -11g+14-20=-11g-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11g+14-20=-11g-6 equation:


Simplifying
-11g + 14 + -20 = -11g + -6

Reorder the terms:
14 + -20 + -11g = -11g + -6

Combine like terms: 14 + -20 = -6
-6 + -11g = -11g + -6

Reorder the terms:
-6 + -11g = -6 + -11g

Add '6' to each side of the equation.
-6 + 6 + -11g = -6 + 6 + -11g

Combine like terms: -6 + 6 = 0
0 + -11g = -6 + 6 + -11g
-11g = -6 + 6 + -11g

Combine like terms: -6 + 6 = 0
-11g = 0 + -11g
-11g = -11g

Add '11g' to each side of the equation.
-11g + 11g = -11g + 11g

Combine like terms: -11g + 11g = 0
0 = -11g + 11g

Combine like terms: -11g + 11g = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3n+10=7(5n-6)-6n | | f^2-4f-23=0 | | 5x+7x-82=146 | | M/4-6=-9 | | 10.01-9.5n=10.2n | | 11x+2(w+1)=5w-6 | | 30A+6B-5C=0 | | 4-x=8-3x | | -5.11+11.6f=-17.52+11.6f+11.77 | | -6(4r+6)+r=-5r-36 | | 18/0.06 | | 6(7-2p)=3(5p-1) | | -18h+12=7-18h | | s^2-26s=11 | | 4x^2=4/9 | | -13r-20-7r=-10+20 | | 8a-3=6a+17 | | 3(x+9)-7=x+10 | | -4p+6=1+p | | 4x/334+(678x+1)=4 | | -(8y-6)-(-7y-7)=4 | | 18y=18y-15 | | h^2-28h-47=0 | | v^2-8=0 | | -5n-32/3=-13/4(13/4n+1) | | 7z+8=2d-7 | | 529+474= | | (t+42)/3=(t+126)/7 | | 5x=12+2+6 | | 2x^1/3=x^-2/3 | | x=3(x+1)-2x | | -11.82+0.8k=2.9k+18.42 |

Equations solver categories